Logistical support of agricultural sector in Ukraine: Legal features - Харитонова, Тетяна Євгенівна; Харитонова, Т. Є.; Харитонова, Татьяна Евгеньевна; Kharytonova, Tetiana Ye.; Каракаш, Ілля Іванович; Каракаш, І. І.; Каракаш, Илья Иванович; Karakash, Illia I.; Григор’єва, Христина Антонівна; Григор’єва, Х. А.; Григорьева, Кристина Антоновна; Hryhorieva, Khrystyna A.; et al. (Centre for Evaluation in Education and Science, 2020)
The article is devoted to the issue of legal regulation of logistical support of Ukrainian agriculture. The relevance of the article is that Ukraine’s agriculture is far behind optimal international norms, and the provision of agriculture with fixed assets does not meet the needs of production. The authors used the dialectical method, the analysis method, the synthesis method, the logical method, the historical method, the method of comparison. As a result of the study, the following conclusions were made that the legislation on state support of agrarians in the sphere of equipment purchased is not substantiated. This is a significant destabilizing factor, as well as insufficiently professional and scientifically substantiated preparation of such regulatory acts. There is an increasing tendency for the use of a “manual regime” for providing state support in agriculture, which is in the situation of instability, is a risky way.

Стаття присвячена питанню правового регулювання матеріально-технічного забезпечення сільського господарства України. Актуальність статті полягає в тому, що сільське господарство України значно відстає від оптимальних міжнародних норм, а забезпечення сільського господарства основними фондами не відповідає потребам виробництва. Автори використовували діалектичний метод, метод аналізу, метод синтезу, логічний метод, історичний метод, метод порівняння. В результаті дослідження було зроблено наступні висновки про те, що законодавство про державну підтримку аграріїв у сфері придбаного обладнання не є обґрунтованим. Це є суттєвим дестабілізуючим фактором, а також недостатньо професійною та науково обґрунтованою підготовкою таких регуляторних актів. Зростає тенденція до використання «ручного режиму» для надання державної підтримки у сільському господарстві, яке в ситуації нестабільності є ризикованим способом.

Статья посвящена проблеме правового регулирования логистического обеспечения сельского хозяйства Украины. Актуальность статьи заключается в том, что сельское хозяйство Украины сильно отстает от оптимальных международных норм, а обеспечение сельского хозяйства основными фондами не покрывает потребности производства. Авторы использовали диалектический метод, метод анализа, метод синтеза, логический метод, исторический метод, метод сравнения. В результате исследования были сделаны следующие выводы о том, что законодательство о государственной поддержке аграриев в сфере закупаемой техники не обосновано. Это значительный дестабилизирующий фактор, а также недостаточно профессиональная и научно обоснованная подготовка подобных нормативных актов. Наблюдается все большая тенденция к использованию «ручного режима» для государственной поддержки сельского хозяйства, что в условиях нестабильности является рискованным способом.
Kharytonova T. Logistical support of agricultural sector in Ukraine: Legal features / T. Kharytonova, I. Karakash, K. Hryhorieva, L. Kanivets, L. Udovyka // Ekonomika Poljoprivrede : Economics of Agriculture. – V. 67 (2). – Centre for Evaluation in Education and Science, 2020. – Р. 511-521.
Keywords: agroindustrial complex; agricultural producers; agriculture; government support; leasing; агропромисловий комплекс; сільськогосподарські виробники; сільське господарство; державна підтримка; лізинг; агропромышленный комплекс; сельхозпроизводители; сельское хозяйство; государственная поддержка; лизинг; Research Subject Categories::LAW/JURISPRUDENCE